Jasmonates: Multifunctional Roles in Stress Tolerance - Ahmad, Parvaiz; Rasool, Saiema; Gul, Alvina; Sheikh, Subzar A.; Akram, Nudrat A.; Ashraf, Muhammad; Kazi, A. M.; Gucel, Salih (Frontiers in Plant Science, 2016)
Jasmonates (JAs) [Jasmonic acid (JA) and methyl jasmonates (MeJA)] are known to take part in various physiological processes. Exogenous application of JAs so far tested on different plants under abiotic stresses particularly salinity, drought and temperature (low/high) conditions have proved effective in improving plant stress tolerance. However, its extent of effectiveness entirely depends on the type of plant species tested or its concentration. The effects of introgression or silencing of different JA- and Me-JA-related genes have been summarized in this review, which have shown a substantial role in improving crop yield and quality in different plants under stress or non-stress conditions. Regulation of JAs synthesis is impaired in stressed as well as unstressed plant cells/tissues, which is believed to be associated with a variety of metabolic events including signal transduction. Although mitogen activated protein kinases (MAPK) are important components of JA signaling and biosynthesis pathways, nitric oxide, ROS, calcium, ABA, ethylene, and salicylic acid are also important mediators of plant growth and development during JA signal transduction and synthesis. The exploration of other signaling molecules can be beneficial to examine the details of underlying molecular mechanisms of JA signal transduction. Much work is to be done in near future to find the proper answers of the questions like action of JA related metabolites, and identification of universal JA receptors etc. Complete signaling pathways involving MAPKs, CDPK, TGA, SIPK, WIPK and WRKY transcription factors are yet to be investigated to understand the complete mechanism of action of JAs.